Policy, Incentives, and Partnership are Keys to Sustaining Food Security, Land Management, Waste Management, and Agrarian Reform - Jonatan Lassa (The Journal of Indonesia Sustainable Development Planning, 2024)
Informed by cases from Southeast Asia (including Indonesia), Pakistan, and Nigeria, this April 2024 Issue puts together an argument that policy, incentives, and partnership are keys to sustaining food security, waste management, land management, and agrarian reform. The political decision to build a new Indonesian Capital in East Kalimantan could mean a positive for boosting local development. However, environmental and potential population pressures can compromise local social environmental settings that challenge the local food system. The article from Cahyono and Tokuda - offers insights into the role of sociodemographic factors as predictors of food security in East Kalimantan, Indonesia. This Issue also covers research on sustainable waste management from Indonesia (Al Muqsit et al. deal with waste management from the views of visitors of a heritage tourism Area in Semarang using a survey) and Nigeria (Ogunseye et al. on how households leverage waste recycling for a green economy based on qualitative studies). The case from Nigeria advocates for policy that promotes equity, incentives, and partnership. Using the PRISMA framework, Gafuraningtyas et al. examine the literature on agrarian reform from Southeast Asia. The authors compared different approaches, including constraints and opportunities in agrarian reform in countries such as Indonesia, the Philippines, Thailand, Timor Leste, and Vietnam. This Issue also offers policy insights into (1) how macroeconomic conditions shape local decentralization and its implication on fiscal capacity in Jambi, Indonesia (Zevaya et al.); (2) how soil organic carbon shapes agriculture, food security, and Health in the context of Pakistan (Amanullah and Khan); And (3) How to know if land management is responsible: Evaluating the 8R framework of responsible land management (de Vries).